PEMETAAN PERSEBARAN LOKASI HOTEL BINTANG 4 DAN 5 SEBAGAI DESTINASI MICE DI WILAYAH KOTA SURABAYA BERBASIS SISTEM INFORMASI GEOGRAFIS - Apdilah, Geddy Kurdo (Jurnal Vokasi Teknik Sipil, 2023)
Surabaya has been nominated as a city that develops MICE (Meeting, Incentive, Conference, Exhibition). As one of the big cities, the development of hotels in Surabaya is considered quite rapid. The development of hotels in Surabaya needs to be balanced with the provision of information. One of the information needed by business people or business travelers who want to carry out MICE activities at this time is the need for geographic information. Geographic Information System (GIS) has a good ability to visualize spatial data and display various sources of information on 4 and 5 star hotel buildings in Surabaya City. This research also uses the nearest neighbor method analysis to determine the distribution pattern of 4 and 5 star hotels in Surabaya City. The results of the distribution pattern analysis using the nearest neighbor method for 4-star hotel locations are manually calculated at 0.829 and from ArcGIS at 0.956. For the location of 5-star hotels, the manual calculation is 0.748 and from ArcGIS is 0.975. From the two methods, it shows that the distribution pattern of 4 and 5 star hotels in Surabaya City gets the same distribution pattern results, namely random distribution patterns.